‘Engaging’ in Gender, Race, Sexuality and (dis)Ability in Science Fiction Television through Star Trek: the Next Generation and Star Trek: Voyager - Porter, Chaya (Université d'Ottawa / University of Ottawa, 2013)
As Richard Thomas writes, “there is nothing like Star Trek…Of all the universes of science fiction, the Star Trek universe is the most varied and extensive, and by all accounts the series is the most popular science fiction ever” (1). Ever growing (the latest Star Trek film will be released in Spring 2013) and embodied in hundreds of novels and slash fanfiction, decades of television and film, conventions, replicas, toys, and a complete Klingon language Star Trek is nothing short of a cultural phenomenon. As Harrison et al argue in Enterprise Zones: Critical Positions on Star Trek, the economic and cultural link embodied in the production of the Star Trek phenomena “more than anything else, perhaps, makes Star Trek a cultural production worth criticizing” (3). A utopian universe, Star Trek invites its audience to imagine a future of amicable human and alien life, often pictured without the ravages of racism, sexism, capitalism and poverty. However, beyond the pleasure of watching, I would ask what do the representations within Star Trek reveal about our popular culture? In essence, what are the values, meaning and beliefs about gender, race, sexuality and disability being communicated in the text? I will explore the ways that the Star Trek universe simultaneously encourages and discourages us from thinking about race, gender, sexuality and disability and their intersections. In other words, this work will examine the ways that representations of identity are challenged and reinforced by Star Trek: The Next Generation and Star Trek: Voyager. This work will situate Star Trek specifically within the science fiction genre and explore the importance of its utopian standpoint as a frame for representational politics. Following Inness, (1999), I argue that science fiction is particularly rich textual space to explore ideas of women and gender (104). As Sharona Ben-Tov suggests in The Artificial Paradise: Science Fiction and American Reality (1995) science fiction’s “position at a unique intersection of science and technology, mass media, popular culture, literature, and secular ritual” offers critical insight into social change (ctd. in Inness 104). I extend Inness and Ben-Tov here to assert that the ways in which science fiction’s rich and “synthetic language of metaphor” illustrate and re-envision contemporary gender roles also offers a re-imagination of assumptions regarding race, sexuality and disability (Inness 104). Extending current scholarship (Roberts 1999, Richards 1997, Gregory 2000, Bernardi 1998, Adare 2005, Greven 2009, Wagner and Lundeen 1998, Relke 2006, and Harrison et all 1996), I intend to break from traditions of dichotomous views of The Next Generation and Voyager as either essentially progressive or conservative. In this sense, I hope to complicate and question simplistic conclusions about Star Trek’s ideological centre. Moreover, as feminist media theorist Mia Consalvo notes, previous analyses of Star Trek have explored how the show constructs and comments on conceptions of gender and race as well as commenting on economic systems and political ideologies (2004). As such, my analysis intends to apply an intersectional approach as well as offer a ‘cripped’ (McRuer 2006) reading of Star Trek in order to provide a deeper understanding of how identities are represented both in science fiction and in popular culture. Both critical approaches – especially the emphasis on disability, sexuality and intersectional identities are largely ignored by past Trek readings. That is to say, while there is critical research on representations in Star Trek (Roberts 1999, Bernardi 1998) much of it is somewhat uni-dimensional in its analysis, focusing exclusively on gender or racialized representation and notably excluding dimensions of sexuality and ability. Moreover, as much of the writing on the Star Trek phenomena has focused on The Original Series (TOS) and The Next Generation this work will bring the same critical analysis to the Voyager series. To perform this research a feminist discourse analysis will be employed. While all seven seasons and 178 episodes of The Next Generation series as well as all seven seasons and 172 episodes of Voyager have been viewed particular episodes will be selected for their illustrative value.
Keywords: Crip Theory; Star Trek; Science Fiction Studies; Critical Disability Studies; Critical Whiteness Studies; Cyborgs; Feminist Media Studies; Whiteness and Science; Women and Science; Postcolonial Theory; Pop Culture Studies; Gender Studies; Indigeneity